Chrysin and flunixin meglumine mitigate overloaded copper-induced testicular and spermatological damages via modulation of oxidative stress and apoptosis in rats - Parlak, Tuba; Seven, Pinar Tatli; Gur, Seyfettin; Gul, Burcu; Yaman, Mine; Seven, Ismail (Wiley, 2022)
This study aimed to evaluate the possible protective actions of chrysin and flunixine meglumine on testicular and spermatological injuries experimentally stimulated by copper. We separated 36 male Sprague-Dawley rats into six equal groups: control, chrysin, flunixine meglumine, copper, copper +chrysin and copper +flunixine meglumine. Chrysin (50 mg/kg/bw/po), flunixine meglumine (2.2 mg/kg/bw/ip) and copper (500 mg/kg/bw/po) were administered day to day for 21 days. Copper administration caused significant morphological, physiological and biochemical alterations compared to the control group, which are as follows: production of oxidative stress, thanks to rise in testis lipid peroxidation and fall in antioxidant enzyme concentrations, decrease in sperm quality and increase in morphologic sperm abnormalities, suppression of spermatogenesis and prominent alterations in the testis histomorphology and induction of apoptosis in the testis tissues. On the other hand, compared to the copper group, treatment with chrysin or flunixine meglumine significantly attenuated these alterations. In conclusion, chrysin and flunixine meglumine have benefits such as antioxidant, antiapoptotic and anti-inflammatory against copper-induced testicular and spermatological damages in rats via the modulation of oxidative stress and apoptosis. Consequently, chrysin is a natural product which has comparable therapeutic actions to flunixine meglumine on the male reproductive system.
Keywords: apoptosis; chrysin; copper; flunixin meglumine; reproductive toxicity